Clinical use of photodynamic therapy in ocular tumors - ÇERMAN, EREN; ÇEKİÇ, OSMAN (ELSEVIER SCIENCE INC, 2015)
Although the introduction of intravitreal anti vascular endothelial growth factor drugs reduced the indications for photodynamic therapy in ophthalmology, it may still be used in various ocular tumors. Although many studies have shown that photodynamic therapy is effective in ocular tumors, the literature consists of case reports and series. In this review, we systematically performed a meta-analysis for the use of photodynamic therapy in circumscribed choroidal hemangioma, diffuse choroidal hemangioma, retinal capillary hemangioma, von Hippel-Lindau angiomatosis, choroidal melanoma, retinal astrocytoma, retinoblastoma, eyelid tumors, conjunctival tumors, and choroidal metastasis. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: photodynamic therapy; ocular tumors; choroidal hemangioma; retinal capillary hemangioma; choroidal melanoma; retinal astrocytoma; retinoblastoma; eyelid tumors; CIRCUMSCRIBED CHOROIDAL HEMANGIOMA; EXUDATIVE RETINAL-DETACHMENT; SQUAMOUS-CELL CARCINOMA; STURGE-WEBER-SYNDROME; EXTERNAL-BEAM IRRADIATION; LIGHT-EMITTING-DIODES; HIPPEL-LINDAU-DISEASE; 5-YEAR FOLLOW-UP; CAPILLARY HEMANGIOMA; INTRAVITREAL BEVACIZUMAB